Reviews of recent publications - various authors (Studies in 20th & 21st Century Literature, 1995)
Elisabeth Bronfen. Over Her Dead Body: Death, Feminity and the Aesthetic by Lisa Maruca Jacques Dupin: Selected Poems. (Translated by Paul Auster, Stephen Romer, and David Shipiro.) by Maryann De Julio Carolyn A. Durham. The Contexture of Feminism: Marie Cardinal and Multicultural Literacy by Yolanda Astarita Patterson Mike Gonzalez and David Treece. The Gathering of Voices: The Twentieth-Century Poetry of Latin America by Steven F. White Emily D. Hicks. Border Writing: The Multidimensional Text by Roselyn Constantino Robin Régine. Socialist Realism: An Impossible Aesthetic by Peter Hitchcock Kari Weil. Androgyny and the Denial of Difference by Brigitte Roussel
Keywords: Elisabeth Bronfen; Over Her Dead Body: Death Feminity and the Aesthetic; Lisa Maruca; Jacques Dupin: Selected Poems; Paul Auster; Stephen Romer; David Shipiro; Maryann De Julio; Carolyn A. Durham; The Contexture of Feminism: Marie Cardinal and Multicultural Literacy; Yolanda Astarita Patterson; Mike Gonzalez; David Treece; The Gathering of Voices: The Twentieth-Century Poetry of Latin America; Steven F. White; Emily D. Hicks; Border Writing: The Multidimensional Text; Roselyn Constantino; Robin Régine; Socialist Realism: An Impossible Aesthetic; Peter Hitchcock; Kari Weil; Androgyny and the Denial of Difference; Brigitte Roussel